Evaluation of cultural competence and antiracism training in child health services. Issue 4 (1st April 2003) - Webb, E; Sergison, M
Abstract : Aims: To evaluate the acceptability and effectiveness of cultural competence and antiracism training to professionals providing services to ill or disabled children. Methods: Immediate post-training and retrospective questionnaire survey of trainees. Main outcome measures were acceptability; perceived relevance to practice; previous training in this area; perceived impact on professionals' confidence in providing care to diverse communities; and reported changes in behaviour and practice. Results: Cultural competence and antiracism training has been neglected in the health sector but is well received by professionals. It is a positive experience for trainees and perceived to be relevant to their practice. Appropriate and non-threatening training in cultural competence changes attitudes, behaviours, and practice, including promoting good practice in communication across linguistic and cultural differences. Conclusions: Appropriate cultural competence and antiracism training is both effective and acceptable in child health services.